Physiogeographical and hydrographical characteristic of Suwałki Landscape Park (north-eastern Poland) - Bajkiewicz-Grabowska, Elżbieta (Oficyna Wydawnicza Instytutu Ekologii PAN, 1993)
A brief description of main relief forms, climatic conditions and river network of Suwałki Landscape Park. The development of river-lake systems (Szeszupa, Szelmentka, Czarna Hańcza) is characterized, morphometric characters of lakes in each system are given.
Pages 7-26 : illustrations ; 24 cm
Bibliographical references (pages 25-26)
Abstract in Polish
Keywords: relief; river-lake network; lakes; Suwałki Lakeland